Waves and Tidal Current on High Tide (Spring Tide Condition) in Rupat Strait Riau Province - Reza Ambar Wati; Rifardi Rifardi; Mubarak Mubarak (Faculty of Fisheries and Marine, Universitas Riau, 2020)
This study was conducted from November 2017 in Rupat Strait, Riau Province. The analysis of model was done in Laboratorium of Physical Oceanography, Departement of Marine Science, Faculty of Fisheries and Marine, University of Riau. The research aims to understand the wave and tidal current on high tide (spring tide condition) in Rupat Strait. The significant wave height is about 0.12-0.90 m/s. The current speed is about 0.18-0.78 m/s. The result of the study indicate that at spring tide condition, the tidal current from Malaka Strait flows up to Rupat Strait by northern and eastern part of Rupat Strait. This condition influences distribution of sediments in Rupat Strait the cause of the changes coastline.